Population Structure and Size at Maturity of the Orange Mud Crab Scylla olivacea in Klong Ngao Mangrove Swamp, Ranong Province, Thailand - Kanchana Jirapunpipat (Agriculture and Natural Resources, 2008)
Population structure and size at maturity of the orange mud crab Scylla olivacea in Klong Ngao mangrove swamp, Ranong Province, Thailand was investigated to derive information for its management. Sampling was carried out monthly during November 2002 to December 2003. The results showed that the large crabs with a carapace width greater than 8 cm, the weight of male is greater than that of female. The small sized mud crabs of both male and female accounted for the major catches while large crabs dominated the lower catches. The size frequency distribution of S. olivacea indicated that the recruitment of this species was continuous throughout the year with males being recruited in larger numbers than females. The proportion of males was significantly higher than that of females with a ratio of 1.3:1 (male: female). The sex ratio of large sized females, with a carapace width greater than 9 cm, varied depending on the spawning period. When 50% of females were mature for the first time their carapace width was 9.55 cm, as estimated from a logistic model.